A Case Study in Indonesıa: Explorıng AI Readıness in Busıness Students Toward Englısh Wrıtıng - Sangaji Yudhi Pratama; Tan Michael Chandra (AL-ISHLAH: Jurnal Pendidikan, 2024)
In the digital era, AI (Artificial Intelligence) finds application in various fields, with education being prominent. In the context of English for Specific Purposes (ESP) practice, AI readiness can potentially enhance learning. The research aimed to investigate students' familiarity with AI and identify the obstacles ESP students face. Moreover, it was a case study research conducted at tertiary level in some universities in Indonesia. The participants in this study were Business English writing students and data were collected through questionnaires and interviews. The results revealed that students were unfamiliar with the use of AI in their environment for various reasons, indicating that they encountered challenges when integrating AI into their learning. Majority students showed a high willingness to use AI in their business English writing learning. Consequently, the research suggests an alternative approach to enhance learning by incorporating AI, , which can help overcome the challenges faced by students in integrating AI into their learning.